2010
DOI: 10.1161/hypertensionaha.110.156141
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Caloric Restriction Prevent Reduction in Cardiac Ca 2+ -Handling Protein Profile in Obese Rats

Abstract: Abstract-Previous studies show that exercise training and caloric restriction improve cardiac function in obesity.However, the molecular mechanisms underlying this effect on cardiac function remain unknown. Thus, we studied the effect of exercise training and/or caloric restriction on cardiac function and Ca 2ϩ handling protein expression in obese rats. To accomplish this goal, male rats fed with a high-fat and sucrose diet for 25 weeks were randomly assigned into 4 groups: high-fat and sucrose diet, high-fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 34 publications
5
58
1
8
Order By: Relevance
“…Over the last decades, several studies have shown that ventricular dysfunction is related to changes in phosphorylation status of sarco/ endoplasmic proteins (LeWinter, 2005;Paulino et al, 2010), reduced sarcoplasmic reticulum Ca 2+ ATPase (SERCA2) function (Pogwizd et al, 2001), upregulation of Na + -Ca 2+ exchanger (NCX) (Pogwizd and Bers, 2002) and diastolic Ca 2+ leak via ryanodine receptors (Ai et al, 2005). We have reported that Ca 2+ handling impairment is associated with ventricular dysfunction and HF progression Medeiros et al, 2008), where both pharmacological (Bartholomeu et al, 2008) and non-pharmacological (Vanzelli et al, 2010) therapies improved cardiac function by minimizing Ca 2+ transient abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, several studies have shown that ventricular dysfunction is related to changes in phosphorylation status of sarco/ endoplasmic proteins (LeWinter, 2005;Paulino et al, 2010), reduced sarcoplasmic reticulum Ca 2+ ATPase (SERCA2) function (Pogwizd et al, 2001), upregulation of Na + -Ca 2+ exchanger (NCX) (Pogwizd and Bers, 2002) and diastolic Ca 2+ leak via ryanodine receptors (Ai et al, 2005). We have reported that Ca 2+ handling impairment is associated with ventricular dysfunction and HF progression Medeiros et al, 2008), where both pharmacological (Bartholomeu et al, 2008) and non-pharmacological (Vanzelli et al, 2010) therapies improved cardiac function by minimizing Ca 2+ transient abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients with metabolic syndrome can show signs of impaired left ventricular function during exercise (17). Furthermore, there is evidence that obesity can alter left ventricular systolic function, which has been attributed to calcium modulation during the cardiac cycle (44). However, in our experimental setting, subjects did not show any sign or symptoms of overt heart failure.…”
Section: Discussionmentioning
confidence: 54%
“…Assessment of cardiac contractile performance in vivo (by echocardiography or invasive LV catheterization), ex vivo (in isolated working hearts) and in vitro (isolated ventricular myocytes) in different animal models of obesity and IR has revealed mechanical abnormalities manifested as prolonged diastolic relaxation, depressed ejection fraction and decreased fractional shortening [15,16,47,48,50,[52][53][54]57,60,[81][82][83][84][85]. The molecular mechanisms underlying abnormal cardiac function in obesity and IR are still not completely understood, but may involve alterations of intracellular Ca 2+ handling since Ca 2+ cycling is the central coordinator of contraction and relaxation during the process of excitation-contraction coupling (ECC).…”
Section: Cardiac Ca 2+ Mishandling In Obesity and Insulin Resistancementioning
confidence: 99%